Basis, Relasi, Ekuilibrium, Aktualisasi, dan Keberlanjutan Wacana Sosok Nietzsche dalam Agama - Herpindo, Herpindo (TRANSFORMATIKA, 2020)
As a philosopher who declares himself an antichrist, Nietzsche has received various criticisms, supports, supports, and even praises from religious circles. Muslims and Christians interested in Nietzsche's various philosophies have created various discourses in the form of figurative language and the like. This research method is qualitative with various interpretive descriptions to reveal Nietzsche's discourse by using the theory of Sawirman's BREAK (2014). The findings of this research show that various labels, titles, and titles have been successful with Nietzsche's figure as a form of rejection, disbelief, hatred, and praise, such as the label "most dangerous philosopher" and also "intellectual leader of the nineteenth century" by the discourse between Christian and Muslim. The extent of the Nieztche discourse also dates from Nazi circles by academics trying to find a connection between Hitler and Nietzsche.